Case of Sister Mary Joseph’s Nodule Inpatient Who Underwent A Whipple Procedure - Ana Lazarova; Antonio Gligorievski; Ivan Nevcev (Crimson Publishers, 2020)
Sister Mary Joseph’s nodule (SMJN) is a metastatic malignancy of the umbilicus which indicates advanced, metastatic disease. Sister Mary Joseph nodule or Sister Mary Joseph Sign refers to a palpable nodule bulging into the umbilicus as a result of metastasis of cancer in the abdomen or the pelvis. It is a rare occurrence, but it is a sign of abdominal cancer, most commonly an adenocarcinoma metastasis from a gastrointestinal (gastric, colonic, pancreatic cancer) or gynecologic primary malignancy. We present the case of a 61-year-old man with an acute, something less than 1cm in diameter non-tender mass located in the umbilicus, diagnostic indication of an SMJN. This patient, 4 months before was diagnosed with pancreatic carcinoma and underwent a Whipple procedure with pathophysiology result of- Adenocarcinoma capitis pancreatic pTNM= pT2 pN1 pMX. This little nodal change in the umbilicus was an indication for further investigation so a computer tomography (CT) scan was done. Our findings are discussed in the following case report.
Keywords: Umbilical nodule; Metastatic cancer; Intra-abdominal cancer; Pancreatic cancer; Sister mary joseph nodule